The enrichment of the Barman model in the achievement of mathematics among first-year intermediate students and their critical thinking skills (Journal of the College of Basic Education, 2025)
The current research aims to know "the effect of the Barman model on the achievement of mathematics among first-year middle school students and their critical thinking skills". The research sample included 63 first-year middle school students for the first semester of the academic year 2023-2024. Al-Rafidain Intermediate School for Boys affiliated to the General Directorate of Education in Baghdad/Karkh 3 was randomly selected. The students were divided into two groups: the control group, which included Section (B) and consisted of 31 students, who were taught in the usual way, and the experimental group, which included Section (C) and consisted of 33 students, who were taught according to the Barman model.The researchers were keen to balance the two groups in terms of the following variables: "chronological age, intelligence, prior knowledge, and previous achievement". The two research tools were prepared, namely the "Mathematical Achievement Test", which consists of 20 objective multiple-choice items, according to the (Merill) classification, which includes three levels: "Remember, Apply, and Discover". The reliability coefficient was calculated using the (Kuder-Richard) equation (RK-20), where the reliability coefficient value reached 86%. A critical thinking test was also prepared, which also consists of 20 objective paragraphs distributed over five skills: inference, interpretation, reasoning, deduction, and evaluation. Using the same equation, a reliability coefficient of 88% was obtained. After completing the experiment, two tests (mathematical achievement and critical thinking skills) were applied to the two groups: the control and the experimental. After collecting the data, appropriate statistical methods were used, and the research results showed the superiority of the students of the experimental group who studied according to the Barman model in both tests (mathematical achievement and critical thinking skills test) compared to the students of the control group. Based on the results, a number of recommendations and suggestions were presented.